'n Literêr-estetiese analise van die Ad Diognetum - Le Roux, Louis Victor (University of the Free State, 1986)
The object of the study is to determine the literary merit of the Ad Diognetum. This is done by way of a stylistic analysis of the script. A critical survey of the various approaches to style in Chapter 1 discloses that the phenomenon 'style' is too complex to encapsulate in a single definition. Consequently, style is described as the selection and arrangement of all usual and unusual elements of a work, which are consciously or unconsciously determined by diverse factors which influence a writer in his communicative situation, which are influenced by the contents of a work, and which have a certain effect, or alternatively, which cause a certain nuance in meaning to be highlighted. The genre, which influences the style and understanding of a work, is then discussed. Apologetic and exhortation motives dominate in the Ad Diognetum. Therefore, it is classified as an apologetic-protreptic script. Language is characterised by stylistic devices. These are described, as well as the levels on which they function; their possible uses, and their incorporation in and collaboration within a text. These devices cause a text to exhibit specific characteristics of style. The smaller constituent elements (nuclear structures, cola and pericopes), on which the analysis is based, are motivated and described. Next the fundamental types (repetitions, omissions, shifts in expectancies, and length of units) under which most of the stylistic devices are categorized, are discussed. The relations in terms of which the functions and meaning of the stylistic devices can be described best, (e.g. the relation of the various parts of the text to each other, and that of the text to the participants in the discourse), then receive attention. In Chapter II a stylistic analysis of each pericope is done on two levels: the semantic and semiotic. The analysis at semantic level involves: i. A motivation for the pericope on thematic and stylistic considerations. ii. Formulating the contents of the cola. iii. A description of the semantic relations between the cola. Hereby the analyst indicates how the pericope should be understood in general. iv. An account of the semantic relations between the nuclear structures by means of which the analyst details his interpretation of the contents of the pericope. The main aim of the analysis on semantic level, therefore, is to indicate how the contents, which influences the style of a script, is understood by the analyst. The semantic relations between the cola and the nuclear structures are those mentioned by Nida et. al. in Style and Discourse, Cape Town, 1983, pp. 102 - 103. The analysis on semiotic level entails: i. Identifying the stylistic devices in the same order as they appear in the text. ii. Describing the functions of the stylistic devices. Chapter III contains an account of the results of a detailed analysis of each pericope. An indication is given of how various stylistic devices in a pericope correspond to accentuate certain concepts and how the quality of the script is being influenced by this. Then follows a summary of the reasoning in the Ad Diogneturn taking into account the stylistic devices which bring to the fore certain nuances of meaning in the pericopes. The relations between the pericopes are indicated. Finally a motivated, positive judgement is passed on the literary merit of the script.
Thesis (D.Litt. (Greek Language))--University of the Free State, 1986
Keywords: Apologetics -- Vroee church, ca. 30-600; Apologetics